Traffic safety and human behavior - Shinar, David (Emerald, 2007)
Traffic crashes have become the epidemic of the third millennium - a seemingly necessary evil that accompanies increasing levels of motorization. In this comprehensive book, Dr David Shinar provides a theoretical framework and a critical evaluation of the most recent research findings to comprehend the complexity of traffic safety and the central role that drivers, motorcyclists, and pedestrians play in it. In approximately 800 pages with over 250 graphs and tables, Shinar covers the key issues that relate human behavior to traffic safety.
Includes indexes.
Keywords: Transportation -- Automotive -- General.; Business & Economics -- Industries -- Transportation.; Road transport industries.; Behavioural economics.; Traffic safety -- Psychological aspects.; elektronické knihy; electronic books